Cancer Anxiety Mediates the Association Between Satisfaction With Medical Communication and Psychological Quality of Life After Prophylactic Bilateral Salpingo-Oophorectomy - Zarbo, Cristina; Brugnera, Agostino; Frigerio, Luigi; Celi, Chiara; Compare, Angelo; Dessì, Valentina; Giordano, Rosalba; Malandrino, Chiara; Sina, Federica Paola; Strepparava, Maria Grazia; Tessitore, Isadora Vaglio; Ventura, Mariangela; et al. (Frontiers in Psychology, 2022)
Background: Prophylactic Bilateral Salpingo-Oophorectomy (PBSO) reduces the risk of developing ovarian cancer. However, the psychological mechanisms that may affect post-surgery quality of life (QoL) among patients who underwent PBSO are still largely unknown. Thus, this study aimed at exploring the direct and indirect associations of satisfaction with medical communication and cancer anxiety on post-surgery QoL among women at high risk of developing ovarian cancer. Method: Fifty-nine women (mean age: 50.64 ± 6.7 years) who underwent PBSO took part in this cross-sectional study, filling out a sociodemographic and clinical questionnaire, a battery of validated psychological measures and an ad hoc developed scale for the assessment of cancer anxiety. We first examined the correlations among all variables of interest, and then tested if cancer anxiety mediated the association between satisfaction with medical communication and post-surgery psychological QoL, controlling both for time from surgery and education. Results: Post-surgery psychological QoL was unrelated from any sociodemographic or clinical variable. Cancer anxiety had a significant direct negative effect on psychological QoL, while satisfaction with medical communication had a significant positive direct effect on it. Finally, cancer anxiety significantly mediated the association between satisfaction with medical communication and post-surgery psychological QoL. Discussion: Results suggest that post-surgery psychological QoL of patients who underwent PBSO may be increased with interventions, delivered in a genetic counselling setting, targeting quality of medical communication and cancer anxiety.